2018
DOI: 10.1520/gtj20170018
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Effects in the Desiccation of Soil Layers with Controlled Environmental Conditions

Abstract: This article presents the results of an experimental research carried to investigate the mechanics of cracking of soil layers under drying conditions. The tests were conducted under controlled laboratory conditions and in an environmental chamber with circular and rectangular specimens to investigate the effect of the boundary conditions (size, shape, and aspect ratio of the specimens and containers) on the process of initiation and propagation of cracks and on the final crack pattern at the end of desiccation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…It should be noted that there is an increase in N T with decreasing layer thickness, representing that the number of cracks initiating at the top surface reduces. This effect of layer thickness on soil surface cracking observed in this study is consistent with the results obtained by previous researchers (Costa et al, 2013; Gui et al, 2016; Guo et al, 2018; Lakshmikantha et al, 2012; Lakshmikantha et al, 2018; Zeng et al, 2019). N B gradually exceeds N T as the layer thickness increases, indicating that more cracks develop from the bottom surface.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that there is an increase in N T with decreasing layer thickness, representing that the number of cracks initiating at the top surface reduces. This effect of layer thickness on soil surface cracking observed in this study is consistent with the results obtained by previous researchers (Costa et al, 2013; Gui et al, 2016; Guo et al, 2018; Lakshmikantha et al, 2012; Lakshmikantha et al, 2018; Zeng et al, 2019). N B gradually exceeds N T as the layer thickness increases, indicating that more cracks develop from the bottom surface.…”
Section: Resultssupporting
confidence: 93%
“…The frictional force generated on the base between soil interlayers applies a significant constraint to the upper soil shrinkage and causes the soil desiccation cracking. In previous studies, some scholars found that the basal friction could affect the stress distribution inside the soil and aggravate soil cracking (Amarasiri & Kodikara, 2013;Gui et al, 2016;Guo et al, 2018;Lakshmikantha et al, 2018;Pouya et al, 2018;Rodríguez, 2006;Sima et al, 2014;Vo et al, 2017;Zeng et al, 2019). So far, most prior studies focus on the evolutions of desiccation cracks initiated at the soil top surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews indicate that using different materials (e.g., glass, wood) as the soil mold influences the size of the desiccated soil clods [34]. Smooth contact surfaces result in smaller width and spacing of the cracking [35], whereas rough interfaces lead to larger extent of cracking and wider crack width distributions [36]. Although the interface roughness was not characterized in this study, we examined the repeatability of the test by comparing results obtained from three parallel samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In the past few decades, desiccation cracking in soil has been widely studied by using both experimental and numerical approaches. Different types of environmental chamber were designed to study cracking in soils as a result of drying/wetting conditions by imposing and monitoring temperature and relative humidity (Cui et al, 2014;Song et al, 2016;Lakshmikantha et al, 2018). Recently, Lozada et al (2018) have presented an advanced climatic chamber which is able to provide accurate and independent control of temperature, relative humidity, solar irradiance, and wind velocity.…”
Section: Introductionmentioning
confidence: 99%